ANALISIS HUKUM TERHADAP TINDAK PIDANA MEMBUKA LAHAN DENGAN CARA MEMBAKAR: LEGAL ANALYSIS OF THE CRIME OF CLEARING LAND BY BURN - Taufiq, Ahmad; Oner, Basri; Yamin, Muhammad Halwan (Clavia, 2021)
The research aims to know: 1) the application of criminal penalties on clearing the land by incinerating as the first alternative indictment in criminal No.27/Pid.b/Lh/2020/Pn.Enr; 2) a judge's legal consideration in rendering a criminal verdict against clearing by searing in a verdict of No.27/Pid.b/Lh/2020/Pn.Enr. The method of research used is qualitative descriptive research by conducting interviews with those involved in the case. Research shows: 1) application of criminal penalties on clearing the land by searing at a verdict of No.27/Pid.b/Lh/2020/Pn.Enr. Has not created a sense of justice for the actions of the accused, who opens the land by searing into the forest preserve, due to a consideration of only aspects of the plantation 2) judge's legal judgment on clearing the land by searing at the verdict No.27/Pid.b/Lh/2020/Pn.Enr, in consideration of this it appears that the judge has not considered a few other factors so as not to reflect a sense of justice for the accused's actions